For equation
"(x - y) y^2 p + (y - x) x^2 q = (x^2 + y^2) z"
write an auxiliary equation
"\\displaystyle\\frac{dx}{y^2(x-y)}=\\displaystyle\\frac{dy}{x^2(y-x)}=\\displaystyle\\frac{dz}{z(x^2+y^2)}\\\\[0.3cm]\n\\displaystyle\\frac{dx}{y^2(x-y)}=\\displaystyle\\frac{dy}{x^2(y-x)}\\rightarrow\\displaystyle\\frac{dx}{y^2}=\\displaystyle\\frac{dy}{x^2(-1)}\\\\[0.3cm]\ny^2dy+x^2dx=0\\rightarrow d\\left(\\frac{x^3}{3}+\\frac{y^3}{3}\\right)=0\\\\[0.3cm]\n\\frac{x^3}{3}+\\frac{y^3}{3}=C_1\\rightarrow x^3+y^3=3C_1\\\\[0.3cm]\n\\boxed{x^3+y^3=c_1}\\\\[0.3cm]\n\\displaystyle\\frac{dx}{y^2(x-y)}=\\displaystyle\\frac{dz}{z(x^2+y^2)}\\rightarrow\n\\displaystyle\\frac{(x^2+y^2)dx}{(x-y)}=\\displaystyle\\frac{y^2dz}{z}\\\\[0.3cm]\n\\int\\left(\\frac{(x^2-y^2)+2y^2}{(x-y)}\\right)dx=\\int\\frac{y^2dz}{z}\\\\[0.3cm]\n\\int\\left(\\frac{(x-y)(x+y)}{(x-y)}+\\frac{2y^2}{(x-y)}\\right)dx=y^2\\ln|z|\\\\[0.3cm]\n\\int\\left(x+y+\\frac{2y^2}{(x-y)}\\right)dx=y^2\\ln|z|\\\\[0.3cm]\n\\boxed{\\frac{x^2}{2}+xy+2y^2\\cdot\\ln|x-y|+c_2=y^2\\ln|z|}"
Then,
"y=0\\rightarrow 0^3+x^3=c_1\\rightarrow\\boxed{x=c_1^{1\/3}}\\\\[0.3cm]\ny=0\\rightarrow\\frac{x^2}{2}+c_2=0\\rightarrow\\boxed{x=(-2x_2)^{1\/2}}\\\\[0.3cm]\nc_1^2=(-2c_2)^3\\\\[0.3cm]\n\\boxed{x^6=\\left(-2\\cdot\\left(y^2\\ln|z|-\\frac{1}{2}\\cdot(x^2-3y^2+2xy+4y^2\\ln|x-y|)\\right)\\right)^3}"
ANSWER
"x^6=\\left(-2\\cdot\\left(y^2\\ln|z|-\\frac{1}{2}\\cdot(x^2-3y^2+2xy+4y^2\\ln|x-y|)\\right)\\right)^3"
Comments
Leave a comment